Between and within-Breed Variations in feed intake and fat deposition, and Genetic Associations of these with some production traits in Menz and Horro Sheep - Ermias, E. (Alemaya University of Agriculture, 1999)
A total of four hundred and fifty seven Menz (n=305) and Horro (n=152) male lambs born over eight consecutive dry- and wet-seasons from October 1992 to July 1996, at ILRI's Debre Berhan Research station were used to: i) determine between-breed differences and within-breed variations in feed intake and fat deposition, and the genetic associations of these with average daily weight gain (ADG), efficiency of feed utilisation (EFU), carcass weight, lean yield and dressing percent and, ii) establish and evaluate equations for predicting total body fat from live animal body measurements. The lambs were fed ad-libitum for about three-and-half months, during which concentrate supplement and hay intake, ADG, EFU and the various live animal measurements were recorded. Lambs were slaughtered at average age of 510 days, where the weights of hot and cold carcass, dissected lean, reticulo-rumen (RRW), individual principal fat depots and total body fat were determined. Dissected fat depots and non-adipose tissues were subjected to ether-extraction to obtain the weights of ether-extracted individual principal adipose tissues and total ether-extracted body fats. Average daily intake of the concentrate supplement did not significantly (P>0.05) differ between the two breeds. However, the Horro exhibited significantly (P<0.01) higher hay DM intake (HayDMI) and total DM intake (TotDMI), the sum of average daily concentrate and hay DM intakes. Apparent feed DM digestibility was lower (P<0.01) in the Horro, while ADG and EFU were similar (P>0.05) in the two breeds. Live weight during ad-libitum feeding was not different (P>0.05) between the two breeds, but the Horro was significantly (P<0.01) taller and longer. Tail was longer (P<0.01, but narrower (P<0.01) at the base in the Horro, as compared to the Menz. Pre-slaughter live weight (PSW) and carcass weights did not significantly (P>0.05) differ between the two breeds. Dissected carcass lean weight was also similar (P>0.05) in the two breeds; but carcass dissected fat weight was significantly (P<0.01) higher in the Menz, and carcass bone weight was significantly higher (P<0.01) in the Horro. Most of the individual principal fat depots and total body fat determined by both dissection and ether-extraction were significantly (P<0.01) heavier in the Menz. Heritability estimates for HayDMI and TotDMI were non-significant because of large standard errors, possibly due to the small data size. Tail and rump fat and abdominal fat weights were highly heritable (0.36 to 0.91), but estimates for the weights of kidney fat, testicular fat, subcutaneous and intermuscular fat and total body fat were non-significant due to large standard errors. Genetic associations involving HayDMI and TotDMI were positive with carcass weight and carcass dissected lean, but non-significant with ADG, EFU and dressing percent. Correlations involving total body fat were non-significant with these production traits. It was suggested that the propensity to fatness in the Menz, and the high hay intake in the Horro may be the most important genetic attributes that enable these breeds adapt to the characteristic variations in quality and quantity of feed in the environment in which these sheep are evolved. It was suggested that the energy reserve of the animal could be genetically improved through direct selection for live animal tail circumference, tail thickness and tail volume, and/or slaughter traits of dissected tail and rump fat, abdominal fat and dissected tail volume. Both dissected and ether-extracted total body fat could also be fairly estimated from multiple regression equation comprising simple live animal body measurements with acceptable precision (R-squared = 0.67 and 0.68) which, at least, allow their use in screening of large number of animals in the field. However, although the equations were quite ''robust'' for they were not significantly (P>0.05) biased by breed, birth type, dam parity and lamb season of birth, heritabilities of, and genetic correlation involving predicted total body fat were non-significant due to large standard errors caused by the small data set.